Circulating miR‐146a and miR‐134 in predicting drug‐resistant epilepsy in patients with focal impaired awareness seizures. (21st April 2020) - Leontariti, Maria; Avgeris, Margaritis; Katsarou, Martha‐Spyridoula; Drakoulis, Nikolaos; Siatouni, Anna; Verentzioti, Anastasia; Alexoudi, Athanasia; Fytraki, Aggeliki; Patrikelis, Panayiotis; Vassilacopoulou, Dido; Gatzonis, Stylianos; Sideris, Diamantis C.
Abstract: Objective: Epilepsy is one of the most prevalent neurologic disorders, causing serious psychological problems and reducing quality of life. Although 20 different antiepileptic drugs (AEDs) have been approved by the US Food and Drug Administration (FDA), 30% of patients have drug‐resistant epilepsy (DRE). Considering the role of miR‐146a and miR‐134 in neuroinflammation and dendritic functionality, respectively, the aim of this study was the clinical evaluation of circulating miR‐146a and miR‐134 as novel noninvasive molecular markers for the prognosis of refractory epilepsy. Methods: The study included 162 patients with focal impaired awareness seizures. Total RNA was extracted from serum samples spiked with synthetic cel‐miR‐39‐3p for normalization purposes. First‐strand complementary DNA (cDNA) synthesis was performed using microRNA‐specific stem‐loop primers, and hsa‐miR‐134/146a levels were quantified by quantitative polymerase chain reaction (qPCR). DRE was used as clinical end point event. Internal validation was performed by bootstrap analysis, and decision curve analysis was used to evaluate the clinical benefit on disease prognosis. Results: The circulating levels of both miR‐134 and miR‐146a were elevated in patients with drug‐resistant seizures. The receiver‐operating characteristic (ROC) curve and logistic regression analysis demonstrated that patients with increased circulating miR‐134/146a levels are at significantly higher risk for developing DRE, independently of temporal lobe sclerosis, epilepsy duration, familial history, age at first seizure, age, body mass index (BMI), smoking behavior, and gender. Finally, decision curve analysis highlighted that the evaluation of circulating miR‐134/146a led to superior clinical benefit for DRE prognosis and patients' risk stratification. Significance: Elevated serum miR‐134/146a levels are associated with a higher risk for AED‐resistant epilepsy and could constitute novel noninvasive molecular markers to improve disease early prognosis and support precision medicine.